2016
DOI: 10.3762/bjoc.12.247
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic synthesis and HPLC–ECD analysis of the isomers of dracocephins A and B

Abstract: Starting from racemic naringenin ((±)-1), a mixture of dracocephin A stereoisomers 6-(2”-pyrrolidinone-5”-yl)naringenin (±)-2a–d and its regioisomer, dracocephin B 8-(2”-pyrrolidinone-5”-yl)naringenin (±)-3a–d originally isolated from Dracocephalum rupestre, have been synthesized in a one-pot reaction. The separation of 2a–d and 3a–d was achieved by preparative HPLC. The four stereoisomers of each natural product were separated by analytical chiral HPLC and their absolute configuration was studied by the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Best agreements were achieved for the CAM‐B3LYP PCM and the B3LYP in vacuo conformers, while the B97D PCM calculations gave the worst agreement with the BH&HLYP and CAM‐B3LYP functionals which were found the best for 4 . This result further supports the importance of the parallel application of various DFT functionals for both the geometry optimization and the ECD calculation steps …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Best agreements were achieved for the CAM‐B3LYP PCM and the B3LYP in vacuo conformers, while the B97D PCM calculations gave the worst agreement with the BH&HLYP and CAM‐B3LYP functionals which were found the best for 4 . This result further supports the importance of the parallel application of various DFT functionals for both the geometry optimization and the ECD calculation steps …”
Section: Resultssupporting
confidence: 73%
“…13,27,31 Acetylcholinesterase inhibitory activity of the products was tested, and rac-7 was found to show moderate AChE inhibitory activity with 35.4% inhibition at 40-μM concentration. The neuroprotective activities of the products were also tested against hydrogen peroxide (H 2 O 2 ), β-amyloid-25-35 fragment (Aβ [25][26][27][28][29][30][31][32][33][34][35] ), and oxygen-glucose deprivation-induced neurotoxicity in human neuroblastoma SH-SY5Y cells. The preliminary screenings showed that rac-3 at 1-μM concentration displayed neuroprotective activity against oxygen-glucose deprivation-induced cellular injuries in human neuroblastoma SH-SY5Y cells with 18.6% increase in cell viability.…”
Section: Computational Sectionmentioning
confidence: 99%
“…These derivatives were prepared by acid-catalyzed regioselective Mannich reaction in which the in situ generated N-acyliminium ion started an electrophile attack to the aromatic A ring of the corresponding flavonoid precursors. Further flavone alkaloids were also synthesized: 8-(2 -pyrrolidinon-5 -il)-quercetin (35) and (−)-epicatechin (37) with the same substituent in position eight (38) and in position six (39), respectively [42,43]. Starting from quercetin (34) compound 35 and its C-6 (36) isomer were obtained in a ratio of 94:6 ( Figure 12).…”
Section: Vindoline and Flavone Derivatives Containing 2-pyrrolidone Ringmentioning
confidence: 99%
“…In order to determine the absolute configuration of the enantiomers of 10a and 11a and correlate it with the characteristic electronic circular dichroism (ECD) transitions, the enantiomers of 10a and 11a were separated by chiral HPLC using Chiralpack IC stationary phase and online HPLC-ECD spectra of the separated enantiomers were recorded. HPLC-ECD measurements aided with time-dependent density functional theory electronic circular dichroism (TDDFT-ECD) calculations represent an efficient method to study the enantiomers in scalemic or racemic mixtures of natural [36,37] or synthetic derivatives [38,39]. The solution TDDFT-ECD approach [40] was applied to determine the absolute configuration of the separated enantiomers by comparing the experimental HPLC-ECD spectra with the computed ones.…”
Section: -Hydride Shift-cyclization Domino Reactionmentioning
confidence: 99%